North Sumatera Cultural Center with Neo Vernacular Approach (International Journal of Architecture and Urbanism, 2023)
The interest of young generation towards traditional arts especially in North Sumatera is fairly low. This is affected by the globalization of medias and the lack of attention the government give for arts and culture despite the fact that this sector can bring more visitors to North Sumatera since the area are famous for their multi-cultural nature. Therefore it is required for North Sumatera to have a proper platform for the youth to better and prosper North Sumatera’s culture such as a Cultural Center. This cultural center can help to accommodate people needs for Art and Cultural platform. The location for this project is located at the old building of “Taman Budaya Sumatera Utara”. Qualitative methods are used in this research including collecting literature studies and buildings as a reference. Located in North Sumatera, a multi-ethnic province, the design of this building will focus on aspects of culture that can be applied in the design using the approach of Neo Vernacular Architecture. Having multi-cultural citizens, using neo vernacular architecture can be a way for architect to connect new art and old art. This building will be a new landmark for North Sumatera to describe it’s beautiful and rich cultures while also providing any needed facilities for arts and culture activities.